Symmetry breaking via internal geometry - Andrew Talmadge (International Journal of Mathematics and Mathematical Sciences)
Gauge theories commonly employ complex vector-valued fields to reduce symmetry groups through the Higgs mechanism of spontaneous symmetry breaking. The geometry of the internal space V is tacitly assumed to be the metric geometry of some static, nondynamical hermitian metric k. In this paper, we consider G-principal bundle gauge theories, where G is a subgroup of U(V,k) (the unitary transformations on the internal vector space V with hermitian metric k) and we consider allowing the hermitian metric on the internal space V to become an additional dynamical element of the theory. We find a mechanism for interpreting the Higgs scalar field as a feature of the geometry of the internal space while retaining the successful aspects of the Higgs mechanism and spontaneous symmetry breaking